2009
DOI: 10.1111/j.1432-2277.2008.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low-dose rituximab on splenic B cells in ABO-incompatible renal transplant recipients

Abstract: Summary The purpose of this study was to assess the effect of a low‐dose rituximab (RIT) at <375 mg/m2 on B cells in the spleen and peripheral blood. Five renal transplant recipients received a single dose of RIT at 10, 15, 35, 150, or 300 mg/m2 3–13 days before transplantation. One patient who received the same immunosuppressive regimen except for RIT was also enrolled as a control. Splenectomy was performed at the time of transplantation in all patients. The B‐cell count in the peripheral blood was analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 23 publications
(68 reference statements)
2
56
0
1
Order By: Relevance
“…Raut et al (23) found no statistically significant difference in the titers of anti-ABO IgM and IgG antibodies between an SPL group and a non-SPL group. Toki et al (24) studied the impact of low-dose RIT on the splenic B cell population in recipients of ABOi kidney transplantation and reported the near-complete depletion of CD20þ from the spleen. Consequently, we have recently abandoned SPL.…”
Section: Discussionmentioning
confidence: 99%
“…Raut et al (23) found no statistically significant difference in the titers of anti-ABO IgM and IgG antibodies between an SPL group and a non-SPL group. Toki et al (24) studied the impact of low-dose RIT on the splenic B cell population in recipients of ABOi kidney transplantation and reported the near-complete depletion of CD20þ from the spleen. Consequently, we have recently abandoned SPL.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous studies, 18 we believe that administration of rituximab at low doses may prevent rejection. Toki and associates 21 reported that administration of a single low dose of RTX, less than the 375 mg/m 2 used in this and previous studies (15,35,150, or 300 mg/m 2 ), had a potent effect, depleting B cells in both the spleen and peripheral blood. 21 We initially administered rituximab at a dose of 375 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Toki and associates 21 reported that administration of a single low dose of RTX, less than the 375 mg/m 2 used in this and previous studies (15,35,150, or 300 mg/m 2 ), had a potent effect, depleting B cells in both the spleen and peripheral blood. 21 We initially administered rituximab at a dose of 375 mg/m 2 . However, we have gradually reduced administration to a single dose of 200 mg as a component of the desensitization protocol, with good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…CD20 is expressed on naive and mature activated B cells as well as some memory B cells. B cell depletion occurs via antibody dependent cytotoxicity and can be rapid, over 3-4 days and sustained, lasing for almost up to a year [9].…”
Section: Anti-cd20 Antibody As Surrogate For Splenectomymentioning
confidence: 99%
“…The optimal dose of rituximab remains unknown. Toki [9] et al studied the effect of B cell depletion with increasing doses of rituximab (10,15,35,150, 300 mg/m 2 ) in 5 patients. All but one dosage of rituximab (10 mg/m 2 ) was able to completely eliminate B cells from circulation in 30 days.…”
Section: Anti-cd20 Antibody As Surrogate For Splenectomymentioning
confidence: 99%